2022
DOI: 10.3390/medicina58101486
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of Single-Port Trans-Axillary Robotic Thyroidectomy: Experience through Consecutive 100 Cases

Abstract: Background and Objectives: Recently, the single-port (SP) robotic system was introduced for minimally invasive operative techniques. Thus, this study aimed to validate the safety and feasibility of SP trans-axillary robotic thyroidectomy (SP-TART) through experiences in a single tertiary institution. Materials and Methods: This study retrospectively analyzed 100 consecutive patients who underwent SP-TART from October 2021 to June 2022 in Seoul St. Mary’s Hospital in Seoul, Korea. We analyzed the clinicopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…These operations were performed via four robotic trocars arranged in the single incision, with one 12 mm trocar for 30-degree dual-camera endoscope, one 8 mm trocar for grasper, and two 5 mm trocars for energy device and dissector, respectively. According to previous studies (Table 3 ) 97 112 , the main advantages of START are ease of console stage, ease of detecting the recurrent laryngeal nerve, ability to perform total thyroidectomy with central and lateral neck dissections for advanced cancer 104 , 106 , 113 , 114 , and more favorable postoperative swallowing function than conventional open thyroidectomy 98 , 113 115 , as well as recognized safety and feasibility 105 , 110 . Especially for oncologic outcomes, Kim et al 112 summarized their experience of 5000 cases of START from October 2007 to May 2016 in a retrospective study, and reported no disease-specific mortality and a median recurrence-free survival of 52.5±27.1 months.…”
Section: The Research Status Of Sirasmentioning
confidence: 99%
“…These operations were performed via four robotic trocars arranged in the single incision, with one 12 mm trocar for 30-degree dual-camera endoscope, one 8 mm trocar for grasper, and two 5 mm trocars for energy device and dissector, respectively. According to previous studies (Table 3 ) 97 112 , the main advantages of START are ease of console stage, ease of detecting the recurrent laryngeal nerve, ability to perform total thyroidectomy with central and lateral neck dissections for advanced cancer 104 , 106 , 113 , 114 , and more favorable postoperative swallowing function than conventional open thyroidectomy 98 , 113 115 , as well as recognized safety and feasibility 105 , 110 . Especially for oncologic outcomes, Kim et al 112 summarized their experience of 5000 cases of START from October 2007 to May 2016 in a retrospective study, and reported no disease-specific mortality and a median recurrence-free survival of 52.5±27.1 months.…”
Section: The Research Status Of Sirasmentioning
confidence: 99%